Documentary on the process of creation in dance: history(ies) and memory(ies) of the body in movement - Wosniak, Cristiane do Rocio (Revista Brasileira de Estudos da Presença, 2021)
This article intend to think on a singular perspective of historical production of/about dance. It is from an interdisciplinary relationship, which involves dance and cinema, that the documentary A Alma do Gesto (2020) is take as an axis and empirical object of investigation in order to analyze creation processes in a dance company as the production of a narrative memorial on gesture and body in motion mediated by digital technology. This study draws on authors who deal with process criticism, memorial archives, history, documentaries and mise-en-scène as a basis for rethinking and deduce that, here, primary documentary sources are crossed by dance fiction.